Perceiving humanness across ages: neural correlates and behavioral patterns - Saito, Toshiki; Nouchi, Rui; Ishibashi, Ryo; Motoki, Kosuke; Matsuzaki, Yutaka; Kobayashi, Akiko; Sugiura, Motoaki; Kawashima, Ryuta (Frontiers in Psychology, 2024)
Humanness perception, which attributes fundamental and unique human characteristics to other objects or people, has significant consequences for people’s interactions. Notably, the failure to perceive humanness in older adults can lead to prejudice. This study investigates the effect of a target’s age on humanness perception in terms of two dimensions: agency (the ability to act and do) and experience (the ability to feel and sense). We also examined brain activity using a magnetic resonance imaging (MRI) scanner in order to understand the underlying neural mechanisms. Healthy university students viewed the facial images of older and younger individuals and judged the humanness of each individual in terms of agency and experience while inside the MRI scanner. The results indicated that older adults were rated higher on experience, and no difference was found in ratings for agency between younger and older face images. Analysis of brain imaging data indicated that positive functional connectivity between the ventral and dorsal regions of the medial prefrontal cortex (mPFC) was greater when judging the humanness of younger faces than older faces. We also found that the negative functional connectivity between the left inferior frontal gyrus and postcentral gyrus was greater when judging the humanness of older faces as compared to that of younger faces. Although the current study did not show distinct brain activities related to humanness perception, it suggests the possibility that different brain connectivities are related to humanness perception regarding targets belonging to different age groups.